Pengaruh Beban Operasi terhadap Nilai Net Plant Heat Rate (NPHR) pada Pembangkit Listrik Tenaga Uap - Herlin Sumarna; Tri Satya Ramadhoni; Gurruh Dwi Septano; Purfaji Purfaji; Toni Okviyanto (Yayasan Literasi Sains Indonesia, 2026)
This study aims to analyze the effect of variations in operating load on the Net Plant Heat Rate (NPHR) at a 3×10 MW coal-fired power plant. The independent variables examined are the generator operating loads at 50%, 75%, and 100%, while the dependent variable is the NPHR value. The research data consists of 30 samples distributed proportionally across each load level. Data analysis was performed using a one-way Analysis of Variance (ANOVA) to test the significance of differences in the mean NPHR values across the operating load variations. The results indicate that variations in operating load significantly affect the NPHR value (p-value < 0.05). The highest average NPHR value was obtained at 50% load at 4160 kcal/kWh, then decreased at 75% load to 3861 kcal/kWh, and reached the lowest value at 100% load at 3625 kcal/kWh. These results indicate that an increase in operating load correlates with a decrease in the NPHR value and an increase in the plant’s thermal efficiency. Thus, operating the coal-fired power plant under conditions approaching optimal design capacity can improve fuel efficiency and support the optimization of the plant’s operational performance.